A clinical case of recurrent pain syndrome due to hiatal hernia, occurring under the guise of acute pancreatitis - A. A. Baulin; L. A. Aver'yanova; V. A. Baulin; O. A. Baulina; D. A. Kompaneytseva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. In the structure of urgent pathology diseases, the leading place belongs to acute pancreatitis, which is the third most common after acute appendicitis and acute cholecystitis. According to statistical data, mild forms of acute pancreatitis account for 84.7%.The aim of the work is to demonstrate a clinical case of recurrent abdominal syndrome occurring under the gastroesophageal mask of acute pancreatitis in order to identify hernia of the esophageal orifice of the diaphragm using the developed diagnostic algorithm.Object and methods. Patient M., 56 years old, repeatedly sought medical help with recurrent abdominal syndrome in a network of polyclinics, as well as a hospital providing emergency specialized medical care. Results and discussion. Against the background of conservative treatment, the patient had a short-term positive dynamics characteristic of a mild form of acute pancreatitis. After taking the patient to the dispensary and conducting an indepth diagnostic examination according to the algorithm developed by our group of researchers, gastroesophageal reflux disease, hernia of the esophageal orifice of the diaphragm was detected.Conclusion. Patients with recurrent abdominal pain syndrome need dispensary observation on an outpatient basis to identify other pathology occurring under the guise of acute pancreatitis and adequate treatment.